Exigências térmicas de Aedes (Stegomyia) albopictus Skuse, 1894 (Diptera, Culicidae) em condições de laboratório - Calado,Daniéla C. (2002)
Thermal requirements of Aedes (Stegomyia) albopictus Skuse, 1894 (Diptera, Culicidae) under laboratory conditions. Allochtonous species of Ae. albopictus in the American continent can be found in fourteen Brazilian states - about fifteen years had been elapsed since the first report of the presence of this species in Brazilian territory. Considering its potential epidemiological importance and its adaptation to several habitats, it was determined, for this species, the threshold temperature and the thermal constant for egg, larval and pupal stages under laboratory conditions under four constant temperatures and 12:12 hours light-dark photoperiod. The threshold temperature for the egg phase and for the first instar were quite similar: 9.07 ºC (K=214.46 degree days) and 9.23 ºC (K= 36.64 degree days), respectively. For 2nd, 3rd and 4th instar, the basal-temperature was higher, oscilating between 12.26 ºC and 13.95 ºC. The threshold temperature for the complete larval stage and for the pupal stage were 12.03 ºC (K= 99.48 degree days) and 11.87 ºC (K=32.40 degree days) for males and 11.95 ºC (K=110.11 degree days) and 11.60 ºC (K=35.30 degree days) for females, respectively.